Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.aca.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Targeted quantification of lipid mediators in skeletal muscles using restricted access media-based trap-and-elute liquid chromatography-mass spectrometry

Abstract: Lipid mediators (LMs) are a class of bioactive metabolites of the essential polyunsaturated fatty acids (PUFA), which are involved in many physiological processes. Their quantification in biological samples is critical for understanding their functions in lifestyle and chronic diseases, such as diabetes, as well allergies, cancers, and in aging processes. We developed a rapid, and sensitive LC-MS/MS method to quantify the concentrations of 14 lipid mediators of interest in mouse skeletal muscle tissue without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Linear regression lines were constructed for each biological matrix versus 5% bovine serum albumin (BSA) in phosphatebuffered saline (PBS, pH 7.4) at 11 concentrations, and linear coefficient values were calculated as presented in Supplementary Table 2. A slope of K = 1 from the linear equation implies correlation and thus demonstrates similar matrix effects exerted by these two matrices [23][24][25][26] . As shown in Supplementary Table 2, the slopes of the linear equations from four sets of solutions are close to unity (0.87-1.12) for these analytes, indicating parallelism of matrix effects presented between the surrogate matrix selected and biological fluids.…”
Section: Resultsmentioning
confidence: 81%
“…Linear regression lines were constructed for each biological matrix versus 5% bovine serum albumin (BSA) in phosphatebuffered saline (PBS, pH 7.4) at 11 concentrations, and linear coefficient values were calculated as presented in Supplementary Table 2. A slope of K = 1 from the linear equation implies correlation and thus demonstrates similar matrix effects exerted by these two matrices [23][24][25][26] . As shown in Supplementary Table 2, the slopes of the linear equations from four sets of solutions are close to unity (0.87-1.12) for these analytes, indicating parallelism of matrix effects presented between the surrogate matrix selected and biological fluids.…”
Section: Resultsmentioning
confidence: 81%
“…To date, profiling and quantification of Wakame GC-MS is a widely used method for the analysis of fatty acids [14]. However, LC-MS has been rarely used but its importance for fatty acid elucidation is increasing [15][16][17][18][19][20][21]. Typically, these methods use a targeted multiple reaction monitoring (MRM) approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…Then we further determined the absolute concentrations of 16 key LMs, related to six metabolic pathways, from mouse skeletal muscles in this study. This quanti cation method, developed in the Brotto Muscle Research Lab in collaboration with the Shimadzu Research Institute, was recently applied and showed substantial differences during aging as well sex related differences in mice [27]. In the present study, both quanti cation and pro ling results indicated signi cant differences (p < 0.05) in LM levels in skeletal muscles of mice infected with P. berghei and P. chabaudi compared to that of the muscles from the control mice (Table 2, Table S1, and Fig.…”
Section: Lipid Signaling Mediators (Lms)mentioning
confidence: 99%
“…The MS/MS analysis was performed on Shimadzu LCMS-8050 triple quadrupole mass spectrometer. The instrument following previously published quanti cation method[27]. All analyses and data processing were completed on Shimadzu LabSolutions V5.91 software (Shimadzu Scienti c Instruments, Inc., Columbia, MD, USA).Tissue preparation for lipidomics analysesStriated muscles were isolated after mice sacri ce, then snap frozen in liquid nitrogen immediately and stored at -80°C.…”
mentioning
confidence: 99%